Kristologi dalam Tradisi Reformasi - Karina Onmilka; Selfina Selfina (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Christology is a branch of theology that studies the person and work of Jesus Christ. In the Reformation tradition, Christology plays a very important role because the teachings about Christ are the main foundation in understanding the salvation of mankind. The Reformation that began in the 16th century in Europe, pioneered by great figures such as Martin Luther, John Calvin, and Huldrych Zwingli, not only brought major changes in the structure of the Church, but also in the way Christians understand and interpret the teachings of Scripture, especially about Christ. This study aims to explore more deeply the understanding of Christology in the Reformation tradition, as well as its impact on the teachings of Christian theology that are developing today. Through a deeper understanding of Christology in the context of the Reformation, it is hoped that readers can gain clearer insight into the differences in views about Christ that exist in various Christian traditions, as well as the contribution of the Reformation in shaping the understanding of modern Christian theology. .